Horizontal transfer of whole mitochondria restores tumorigenic potential in mitochondrial DNA-deficient cancer cells - Dong, Lan-Feng; Kovarova, Jaromira; Bajzikova, Martina; Bezawork-Geleta, Ayenachew; Svec, David; Endaya, Berwini; Sachaphibulkij, Karishma; Coelho, Ana R; Sebkova, Natasa; Ruzickova, Anna; Tan, An S; Kluckova, Katarina; et al. (eLife, 2017)
Recently, we showed that generation of tumours in syngeneic mice by cells devoid of mitochondrial (mt) DNA (ρ0 cells) is linked to the acquisition of the host mtDNA. However, the mechanism of mtDNA movement between cells remains unresolved. To determine whether the transfer of mtDNA involves whole mitochondria, we injected B16ρ0 mouse melanoma cells into syngeneic C57BL/6Nsu9-DsRed2 mice that express red fluorescent protein in their mitochondria. We document that mtDNA is acquired by transfer of whole mitochondria from the host animal, leading to normalisation of mitochondrial respiration. Additionally, knockdown of key mitochondrial complex I (NDUFV1) and complex II (SDHC) subunits by shRNA in B16ρ0 cells abolished or significantly retarded their ability to form tumours. Collectively, these results show that intact mitochondria with their mtDNA payload are transferred in the developing tumour, and provide functional evidence for an essential role of oxidative phosphorylation in cancer.
Keywords: Animals; přenos genů horizontální; respiration recovery; tumour growth; Cell Line, Tumor; DNA, Mitochondrial; buněčné dýchání; mitochondrial transfer; Gene Transfer, Horizontal; melanom; modely nemocí na zvířatech; myši inbrední C57BL; mitochondriální DNA; Cell Respiration; Melanoma; Disease Models, Animal; mouse; zvířata; Mice, Inbred C57BL; nádorové buněčné linie; cancer biology